Corruption and Public Budgeting in the Local Government in Indonesia - Sunarti, S; Susilo, Totok; Sriyanto, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
The trend of corruption cases by regional heads and members of the Regional House of Representatives increased after the reform. In 2004-2017 there were 392 Regional Heads involved in legal issues, the largest number of corruption cases were 313 cases. Indonesia consists of 34 provinces with diverse demographic structures and also various public problems. The research objective was to analyze the effect of misuse of public budgets on the level of corruption in Indonesia. A large enough of public budget tends to trigger corruption in Indonesia. This research is useful for regional governments to be more transparent and accountable in the use of public budgets. In addition, this research is useful for policy makers to make better control tools. The data collection consisting of regional government financial reports that have been audited by the Supreme Audit Board in Indonesia. Reports LG financial reports will be analyzed to determine the amount of public budget in each region, the amount of regional loss from regulatory non-compliance and the level of corruption in Indonesia. This research applied panel data using the help of Eviews 8 application for data processing. The results of this research indicated that the public budgeting does not affect the level of corruption in the local government of Indonesiain. In this study the public budget is measured by the amount of funds or costs for the public, so it does not affect the level of corruption. The amount of funds budgeted to the public does not affect the level of corruption. corruption of public budgets is influenced by transparency and accountability in the use of public budgets.